A novel small molecule, Rosline, inhibits growth and induces caspase‐dependent apoptosis in human lung cancer cells A549 through a reactive oxygen species‐dependent mechanism. (6th April 2016) - Zhao, Ting; Feng, Yang; Jin, Wenling; Pan, Hui; Li, Haizhou; Zhao, Yang
Abstract: Chemical screening using synthetic small molecule libraries has provided a huge amount of novel active molecules. It generates lead compound for drug development and brings focus on molecules for mechanistic investigations on many otherwise intangible biological processes. In this study, using non‐small cell lung cancer cell A549 to screen against a structurally novel and diverse synthetic small molecule library of 2, 400 compounds, we identified a molecule named rosline that has strong anti‐proliferation activity on A549 cells with a 50% cell growth inhibitory concentration (IC50 ) of 2.87 ± 0.39 µM. We showed that rosline treatment increased the number of Annexin V‐positive staining cell, as well as G2/M arrest in their cell cycle progression. Further, we have demonstrated that rosline induces a decrease of mitochondrial membrane potential (Δφm ) and an increase of caspases 3/7 and 9 activities in A549 cells, although having no effect on the activity of caspase 8. Moreover, we found that rosline could induce the production of reactive oxygen species (ROS) and inhibit the phosphorylation of signaling molecule Akt in A549 cells. Alternatively, an antioxidant N‐acetyl‐L‐cysteine (NAC) significantly attenuated rosline's effects on the mitochondrial membrane potential, caspases 3/7 and 9 activities, cell viabilities and the phosphorylation of Akt. Our results demonstrated that ROS played an important role in the apoptosis of A549 cells induced by rosline.